The baby-sitters club. 2, The truth about Stacey - Telgemeier, Raina; Martin, Ann M., 1955-; Lamb, Braden (New York : Graphix, 2015)
Joining the Baby-sitter's Club after moving to a new town, Stacey helps her new friends outmaneuver a rival sitter group while coming to terms with her diabetes.
Based on: The truth about Stacey / Ann M. Martin.
Keywords: Babysitters Club -- (Imaginary organization) -- Comic books, strips, etc; Babysitters -- Comic books, strips, etc; Clubs -- Comic books, strips, etc; Diabetes -- Comic books, strips, etc; Graphic novels